Discrete breathers in a triangular β-Fermi-Pasta-Ulam-Tsingou lattice; Physical Review E; Vol. 103, iss. 5 - Babicheva R. I. Rita; Semenov A. S.; Soboleva E. G. Elvira Gomerovna; Kudreyko A. A. Aleksey Alfredovich; Zhou Kun; Dmitriev S. V. Sergey Vladimirovich (2021, 2021)
Title screen